Organic agriculture for sustainable livelihoods - Halberg, N.; Müller, A (CTA / Earthscan, 2013)
Aiming to inspire the organic movements, as well as policy-makers, researchers and others outside the sector, this text provides a timely assessment of the potential of organic agriculture (OA) for rural development and the improvement of livelihoods. It covers market-oriented approaches and challenges for OA, and demonstrates roles that organic farming can play in (among others) climate change, food security, carbon sequestration, human health and the restoration of degraded landscapes.